Unmasked: when a clinically malignant disease turns out infectious : a rare case of tularemia - Bulut, Cem; Dyckhoff, Gerhard; Penzel, Roland; Plinkert, Peter K.; Simon, Christian; Weichert, Wilko; Stenzinger, Albrecht (International journal of surgical pathology, 2013)
This article reports on a 62-year-old man, who presented with cervical mass and rather nonspecific symptoms. The medical history and clinical workup initially favored a malignant disease such as a carcinoma of unknown primary as the underlying cause. Eventually, the patient was diagnosed with a granulomatous lymphadenitis caused by Francisella tularensis subsp holarctica. Tularemia is a rare disease in Western Europe and can present in multiple ways encompassing almost asymptomatic infections and fatal disease. A rapid diagnosis is often hampered by nonspecific symptoms and the generally low prevalence and incidence of this disease in endemic countries. This case report also provides a comprehensive review of the literature on cervical tularemia and discusses the differential diagnoses.
Gesehen am 20.06.2018
First published June 6, 2012